Derivation and Preliminary Validation of a Risk Score to Predict 30-Day Emergency Department Revisits for Sickle Cell Pain - Glassberg, Jeffrey (Am J Emerg Med, 2015)
BACKGROUND: ED revisits and 30-day readmissions have been proposed as markers for quality-of-ED-care for Sickle Cell Disease (SCD). OBJECTIVE: To create a scoring system that quantifies the risk of 30-day revisit after ED discharge for SCD vaso-occlusive pain METHODS: This was a dual-center retrospective derivation and validation cohort study. The derivation was performed at an academic, tertiary care center and the validation at an urban community hospital. The primary outcome was revisit to the ED within 30-days after an ED discharge for SCD pain. Recursive partitioning was used to derive a scoring system to predict 30-day revisits. RESULTS: Of a total 1456 ED visits for SCD pain, there were 680 ED discharges (admission rate of 53%) in 193 unique individuals included in the derivation cohort. There were 240 (35.3%) 30-day revisits. Of a total 126 ED visits for SCD there were 79 ED discharges in 41 unique individuals in the validation cohort. The final risk score included 4 variables: 1) age, 2) insurance status, 3) triage pain score and 4) amount of opioids administered during the ED visit. Possible scores range from 0–6. The areas under the receiver operating characteristic curves were 0.746 (95% CI 0.71–0.78 - derivation cohort) and 0.753 (95% CI 0.65 – 0.86 – validation cohort). A cutoff of 4 or greater identified 60% of 30-day ED revisits in the derivation cohort and 80% of revisits in the validation cohort. CONCLUSIONS: A risk score can identify ED visits for SCD pain with high risk of 30-day revisit.